Comparison of COVID−19-associated inpatient burden by variant period in hospitalized children age <5 years in the United States - Kathleen M. Andersen; Maria D. McColgan; Alejandro Cane; Mary M. Moran; Maya Reimbaeva; Santiago M. C. Lopez (Frontiers in Pediatrics)
IntroductionThis study evaluated clinical outcomes in children aged <5 years with COVID−19-associated hospitalizations and assessed whether disease severity differed across periods of SARS-CoV-2 variant predominance in the United States.MethodsData from the PINC AI™ Healthcare Database during three distinct periods of SARS-CoV-2 variant predominance [pre-Delta (April 2021–June 2021), Delta (July 2021–December 2021), and Omicron (January 2022–July 2023)] were used. Hospital length of stay (LOS), admission to the intensive care unit (ICU), ICU LOS, usage and duration of oxygen supplementation, usage and duration of invasive mechanical ventilation (IMV), and inpatient death were assessed for each period.ResultsOverall, 10,316 children aged <5 years were hospitalized for COVID-19 over the three periods. Most pediatric COVID-19 hospitalization occurred during the Omicron period. In each time period, children aged <1 year were disproportionately affected. For each outcome of interest, there were no statistically significant differences between variant periods. Similar proportions of hospitalized children required oxygen supplementation (pre-Delta 13%; Delta 16%; Omicron 18%), required IMV (pre-Delta 7%; Delta 8%; Omicron 7%) and experienced in-hospital death (pre-Delta 0.7%; Delta 0.9%; Omicron 0.4%). Duration of hospital LOS, ICU LOS and IMV use were also similar.ConclusionsDespite perception that the omicron variant is less severe, children aged <5 years have a similar risk of severe COVID-19 as they did in earlier variant eras. These results highlight the need for continued preventative measures against severe COVID-19 in children, including routine immunization for eligible children and pregnant people with an updated COVID-19 vaccine.